2017
DOI: 10.1111/jam.13556
|View full text |Cite
|
Sign up to set email alerts
|

Multi-effect of the water-solubleMoringa oleiferalectin againstSerratia marcescensandBacillussp.: antibacterial, antibiofilm and anti-adhesive properties

Abstract: Taking together, our results provide support to the potential use of WSMoL for controlling biofilm formation by bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 48 publications
0
21
0
4
Order By: Relevance
“…Some lectins also interfere with bacterial cell wall permeability. For example, one study conducted by Moura et al demonstrated that use of water soluble lectin from seeds of M. oleifera against corrosive bacteria caused leakage of intracellular proteins due to the loss of wall/membrane integrity in a dose dependent manner (Moura et al, 2017). Apart from the bactericidal and bacteriostatic effect, plant lectins also inhibit bacterial biofilm formation.…”
Section: Antibacterial Activity Of Plant Lectinsmentioning
confidence: 99%
“…Some lectins also interfere with bacterial cell wall permeability. For example, one study conducted by Moura et al demonstrated that use of water soluble lectin from seeds of M. oleifera against corrosive bacteria caused leakage of intracellular proteins due to the loss of wall/membrane integrity in a dose dependent manner (Moura et al, 2017). Apart from the bactericidal and bacteriostatic effect, plant lectins also inhibit bacterial biofilm formation.…”
Section: Antibacterial Activity Of Plant Lectinsmentioning
confidence: 99%
“…Although there is no clear mechanism, there is evidence that the plant's antimicrobial activity is related to a wide spectrum of bactericidal substances produced by the plant (Kostova and Dinchev, 2005;Viera et al, 2010). However, the seeds of M. oleifera also contain a water-soluble lectin called (WSMoL), which was previously reported to have antibacterial effects (Moura et al, 2015(Moura et al, , 2017Coriolano et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Uma lectina solúvel em água isolada das sementes de M. oleifera (WSMoL) tem demonstrado atividade inseticida, [5][6][7] e estudos in vitro demonstraram sua atividade antibacteriana contra bactérias corrosivas e patogênicas. [8][9][10] A WSMoL demonstrou atividade anti-inflamatória in vitro em macrófagos murinos estimulados por lipopolissacarídeos, 11 e foi capaz de ativar linfócitos humanos a partir de culturas de células mononucleares do sangue periférico, mostrando um efeito imunomodulador. 12 Também tem sido comprovado que WSMoL é uma das proteínas coagulantes encontradas nas sementes de M. oleifera, 8,13 e é capaz de reduzir a turbidez e a ecotoxicidade de amostras de água coletadas de um riacho poluído.…”
Section: Introductionunclassified